Identifikasi Kegagalan Peralatan Proteksi Pada Jaringan Distribusi PT. Pln Gardu Induk Garuda Sakti Menggunakan Anfis (Adaptive Neural Fuzzy Inference System) - Devi Juliana; Eddy Hamdani; Edy Ervianto (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2015)
The purpose of research is to identification process of faulty protection devices using operating status of circuit breaker. Technique used for the identification process is Adaptive Neuro-Fuzzy Inference System (ANFIS). ANFIS is a method that combines fuzzy logic and neural network. Design ANFIS needs input data in form of voltage, current and operating status of circuit breaker (1 and 0) for training process. Input data produces by output of distribution system simulation in ETAP, meanwhile operating status of circuit breakers in binary numbers, one and zeros are interpreted as operating and non-operating devices, respectively. The training result gives worth accuracy so that can be use for predicting operating status of circuit breaker. If faulty device has been identified so system restoration can be done immediately.Keywords: ANFIS; distribution system; faulty protection devices; circuit breaker